Literature Review: The Potential of Local Alternative Feeds for Sustainable Pig Farming in Tana Toraja - Ruli, Fitha Febrilia; Khalidatunnisa, Besse (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Pig farming in Tana Toraja, Indonesia, plays a crucial role in both food security and socio-cultural traditions. However, the rising cost of commercial feed poses a significant challenge for farmers, driving the need for affordable alternative feed sources. This literature review aims to evaluate the potential of locally available alternative feed sources in Tana Toraja, focusing on cassava peels, banana stems, and sweet potato leaves, to provide a sustainable and affordable solution for pig farmers in the region. The study was conducted through a systematic analysis of scientific literature to assess the nutritional composition, benefits, and limitations of these alternative feeds. The results indicate that incorporating these local resources can enhance the nutritional profile of pig feed, leading to improved average daily weight gain and feed conversion ratio. Furthermore, their utilization can promote better gut health, which supports growth performance. Nevertheless, the use of these local feeds faces various challenges, including the presence of anti-nutritional factors, high crude fiber content, and low crude protein levels, which are crucial for pig growth. Therefore, this review emphasizes the importance of using appropriate processing methods, as well as supplementing enzymes and specific compounds to optimize the nutritional value of these local feeds. This review is essential as a comprehensive reference for pig farmers in Tana Toraja to utilize local alternative feeds to overcome high feed costs while supporting environmental sustainability by utilizing agricultural waste.